Renal and hypothalamic inflammation in renovascular hypertension: role of afferent renal nerves - Lauar, Mariana R. [UNESP]; Evans, Louise C.; Van Helden, Dusty; Fink, Gregory D.; Banek, Christopher T.; Menani, José V. [UNESP]; Osborn, John W. (American Physiological Society, 2023)
Renal denervation (RDN) is a potential therapy for drug-resistant hypertension. However, whether its effects are mediated by ablation of efferent or afferent renal nerves is not clear. Previous studies have implicated that renal inflammation and the sympathetic nervous system are driven by the activation of afferent and efferent renal nerves. RDN attenuated the renal inflammation and sympathetic activity in some animal models of hypertension. In the 2 kidney,1 clip (2K1C) model of renovascular hypertension, RDN also decreased sympathetic activity; however, mechanisms underlying renal and central inflammation are still unclear. We tested the hypothesis that the mechanisms by which total RDN (TRDN; efferent þ afferent) and afferent-specific RDN (ARDN) reduce arterial pressure in 2K1C rats are the same. Male Sprague-Dawley rats were instrumented with telemeters to measure mean arterial pressure (MAP), and after 7 days, a clip was placed on the left renal artery. Rats underwent TRDN, ARDN, or sham surgery of the clipped kidney and MAP was measured for 6 wk. Weekly measurements of water intake (WI), urine output (UO), and urinary copeptin were conducted, and urine was analyzed for cytokines/chemokines. Neurogenic pressor activity (NPA) was assessed at the end of the protocol calculated by the depressor response after intraperitoneal injection of hexamethonium. Rats were euthanized and the hypothalamus and kidneys removed for measurement of cytokine content. MAP, NPA, WI, and urinary copeptin were significantly increased in 2K1C-sham rats, and these responses were abolished by both TRDN and ARDN. 2K1C-sham rats presented with renal and hypothalamic inflammation and these responses were largely mitigated by TRDN and ARDN. We conclude that RDN attenuates 2K1C hypertension primarily by ablation of afferent renal nerves which disrupts bidirectional renal neural-immune pathways. NEW & NOTEWORTHY Hypertension resulting from reduced perfusion of the kidney is dependent on renal sensory nerves, which are linked to inflammation in the kidney and hypothalamus. Afferent renal nerves are required for chronic increases in both water intake and vasopressin release observed following renal artery stenosis. Findings from this study suggest an important role of renal sensory nerves that has previously been underestimated in the pathogenesis of 2K1C hypertension.
Keywords: afferent renal nerves; hypothalamus; renal inflammatory cytokines; renovascular hypertension; sympathetic pressor activity